New Red-Shifted 4-Styrylcoumarin Derivatives as Potential Fluorescent Labels for Biomolecules - Eustáquio, R (2022)
Important scientific areas, such as cellular biology, medicine, pharmacy, and environmental sciences, are dependent on very sensitive analytical techniques to track and detect biomolecules. In this work, we develop a simple, low-cost and effective synthetic strategy to produce new red-shifted 4-styrylcoumarin derivatives as promising inexpensive fluorescent labels for biomolecules. The extension of the delocalized -electron system results in bathochromic shifts in these new coumarin derivatives, which also present large Stokes shifts. In addition, density functional theory and timedependent density functional theory calculations helped to rationalize the photophysical properties observed by the experimental results.